Response of Inoculated Finger Pepper (Capsicum Annuum Var. Longum) Applied with Different Fertilizer Materials - ANGEL D. ALVAREZ; MARK ALLAN L. FLORES (International Journal of Multidisciplinary Research and Studies, 2023)
A pot experiment was conducted to determine the growth and yield performance of inoculated finger pepper with different fertilizer materials. A 2x4 factorial in split plot design in a randomized complete block design (RCBD) with four replications was employed in this study. The factors include the inoculants (A1 – with inoculant and A2 – without inoculant) and the different fertilizer materials (B1- control, B2- farmer’s practice, B3- vermicast and B4- fortified organic fertilizer). The collected data were analyzed using Statistical Tool for Agriculture Research (STAR) and significant results were subjected to statistical analysis using the Least Significant Difference (LSD) Test. The results reveal that the application of root inoculant (A1) significantly shorten the number of days from transplanting to harvesting and the number of days from transplanting to flowering. While treatment B3 (vermicast) gave the highest growth characteristics and yield components. Treatment supplemented with vermicast and fortified organic fertilizer gave the same positive effect on the height at maturity, number of days from transplanting to harvesting, number of days from transplanting to flowering, flowering to fruiting, fruiting to harvesting compared with control (B1), and farmer’s practice (B2). It has an interaction effect between root inoculants and different fertilizer materials on the number of fruits per plant, the weight of fruits per plant, the diameter of fruit, the length of fruit, and the computed yield per 1000 pot plants.